3D printed simulation models based on real patient situations for hands‐on practice. (29th July 2016) - Kröger, E.; Dekiff, M.; Dirksen, D.
Abstract: During the last few years, the curriculum of many dentistry schools in Germany has been reorganised. Two key aspects of the applied changes are the integration of up‐to‐date teaching methods and the promotion of interdisciplinarity. To support these efforts, an approach to fabricating individualised simulation models for hands‐on courses employing 3D printing is presented. The models are based on real patients, thus providing students a more realistic preparation for real clinical situations. As a wide variety of dental procedures can be implemented, the simulation models can also contribute to a more interdisciplinary dental education. The data used for the construction of the models were acquired by 3D surface scanning. The data were further processed with 3D modelling software. Afterwards, the models were fabricated by 3D printing with the PolyJet technique. Three models serve as examples: a prosthodontic model for training veneer preparation, a conservative model for practicing dental bonding and an interdisciplinary model featuring carious teeth and an insufficient crown. The third model was evaluated in a hands‐on course with 22 fourth‐year dental students. The students answered a questionnaire and gave their personal opinion. Whilst the concept of the model received very positive feedback, some aspects of the implementation were criticised. We discuss these observations and suggest ways for further improvement.